Patient Care in the Obstetrics and Gynecology Department, Nursery Role - Marwah Saeed Almudayris; Fatimah Adnan Alghafli; Amnah Adnan Alghafli; Amnah Mohammed Alfarhan; Alsaqer, Shahrazad Ramadhan M; Faisal Sultan Alnowiser; Abdulaziz Ibrahim Alrubya; Yazeed Ali Alkubais; Khawlah Ahmed Alali; Saja Abdullah Al Khualif; Mahdi Abdulkareem Abdullah Alsubi; Modaher Habib Hassan Alhashem‏; et al. (International Journal of Scientific Research and Innovative Studies, 2023)
Patient care in the obstetrics and gynecology (OB/GYN) department is a multifaceted process that requires collaboration among various healthcare professionals to ensure the well-being of women throughout all stages of their reproductive health journey. The nursery, as an integral component of the OB/GYN department, plays a crucial role in providing specialized care and support to newborns and infants. This review examines the functions, responsibilities, and contributions of the nursery to maternal and neonatal health outcomes within the OB/GYN department, drawing upon relevant literature